The impact of realistic and illusory control on psychological distress: A test of the model of instrumental realism - Whelan, Christopher T. (Economic & Social Studies, 1992)
This paper explores the relationship between sense of control and psychological distress. Rather than providing evidence for the view that rejection of responsibility for outcomes has a beneficial effect on the mental health of low status groups, our findings suggest that increments of control have their most dramatic effect among those with low status and resources. The results reported are consistent with the existence of a threshold of dysfunction beyond which point increased feelings of control are detrimental to one's well-being. Unlike previous research, though, this threshold effect was found to apply to both realistic and illusoty control.
Keywords: control; psychological distress; instrumental realism